Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1128/jvi.03029-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Enterovirus 71 Uncoating Captured at Atomic Resolution

Abstract: Human enterovirus 71 (EV71) is the major causative agent of severe hand-foot-and-mouth diseases (HFMD) in young children, and structural characterization of EV71 during its life cycle can aid in the development of therapeutics against HFMD. Here, we present the atomic structures of the full virion and an uncoating intermediate of a clinical EV71 C4 strain to illustrate the structural changes in the full virion that lead to the formation of the uncoating intermediate prepared for RNA release. Although the VP1 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 47 publications
5
87
1
Order By: Relevance
“…Virus Purification-EV71 and the recombinant viruses (EV71-NE1 and EV71-N6) were all grown and purified as described previously (20). The virions and empty particles were separated by sedimentation through a discontinuous 10 -50% sucrose gradient by no-brake ultracentrifugation at 26,000 rpm for 3 h. Fractions were collected and resolved by 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Virus Purification-EV71 and the recombinant viruses (EV71-NE1 and EV71-N6) were all grown and purified as described previously (20). The virions and empty particles were separated by sedimentation through a discontinuous 10 -50% sucrose gradient by no-brake ultracentrifugation at 26,000 rpm for 3 h. Fractions were collected and resolved by 12% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…2, A-C). Biochemical analyses showed that the empty particle contains VP0, VP1 (or mutant VP1), and VP3, whereas the virion contains VP1-4 (20). EM analyses showed that the empty particle exhibits only an empty shell, whereas the virion displays a dark center within the shell due to the RNA genome inside (Fig.…”
Section: Generation Of Ev71 Recombinantmentioning
confidence: 99%
See 3 more Smart Citations